Original Research: Nurses' Knowledge and Comfort with Assessing Inpatients' Firearm Access and Providing Education on Safe Gun Storage. Issue 9 (September 2020) - Sheppard, Kimberly Smith; Hall, Kathryn; Carney, Julia; Griffith, Catherine; Rudolph, Meaghan; Zelinsky, Megan; Gettings, Elise
ABSTRACT: Purpose: This study sought to evaluate nurses' knowledge and comfort with assessing inpatients' access to firearms and providing education on firearm safety and storage. Facilitators and barriers to such assessment, as well as best methods for educating nurses and patients on firearm safety and storage, were also explored. Methods: Nurses from a general medical unit and a psychiatric unit at a large urban hospital were invited to complete a 22-question online survey. Descriptive statistics were computed to analyze survey responses for each unit. Results: Forty-two nurses—21 from each unit—participated. More than 50% of nurses on each unit were unfamiliar with state law on safe gun storage, and none had prior training in educating others on firearm safety and storage. Compared with nurses on the psychiatric unit, those on the general medical unit were less comfortable asking patients about firearm access and safe gun storage. Several facilitators and barriers to assessment emerged. Facilitators identified by similar numbers of nurses on each unit included receiving relevant education and having educational information available for patients. Nurses on both units also endorsed having a safety protocol and a documentation policy in place. Barriers identified by similar numbers of nurses on each unit included lack of adequate knowledge about firearm safety and lack of patient educational materials. More medical unit than psychiatric unit nurses also named lack of time and not knowing what to do with collected information. More than 80% of nurses on each unit reported that they would feel comfortable providing patients with information on safe firearm storage if it were available; a pamphlet was endorsed most often as the best method. A one-hour class involving the security department and other disciplines was the top endorsed nurse learning strategy. Conclusions: Findings from this study highlighted several factors, including nursing specialty, that may influence inpatient assessment of firearm access and safe gun storage. These results can help inform hospital policies and nursing education initiatives aimed at improving safe gun storage practices among patients and the general public. Abstract : The authors sought to determine hospital nurses' knowledge of firearm safety and current state law, and their comfort with asking patients about gun access and educating them on gun safety.